2018
DOI: 10.1007/s40152-018-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Well-Being, Resilience and Stress Amongst a Sample of Merchant Seafarers and Superintendents

Abstract: Marine spatial planning (MSP) now has a sufficient history for consideration of the way in which MSP processes are developing over time, gaining experience and responding to issues that arise. Rather than setting a study of this kind in the well-established framework of adaptive management, I choose instead a spatial concept that allows planning action to be more closely meshed with the nature of the marine setting itself, that of Deleuze and Guatarri's notion of striated and smooth spaces. This suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Vigilance demands were associated with sleep problems and had a strong significant effect on chronic fatigue [ 67 ], whilst physical work demands predicted high stress in surface fleet personnel but not submariners [ 46 ] and psychological demands significantly predicted fatigue [ 30 ]. Other specific job demands cited as stressors included too many unnecessary emails from shore office to vessels; difficulties coordinating with different stakeholders such as charters, port operators, and managers; and too many unnecessary and unstructured safety meetings [ 68 ]; additionally, in this study being under-staffed was reported to lead to greater job demands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigilance demands were associated with sleep problems and had a strong significant effect on chronic fatigue [ 67 ], whilst physical work demands predicted high stress in surface fleet personnel but not submariners [ 46 ] and psychological demands significantly predicted fatigue [ 30 ]. Other specific job demands cited as stressors included too many unnecessary emails from shore office to vessels; difficulties coordinating with different stakeholders such as charters, port operators, and managers; and too many unnecessary and unstructured safety meetings [ 68 ]; additionally, in this study being under-staffed was reported to lead to greater job demands.…”
Section: Resultsmentioning
confidence: 99%
“…Participants reported long monotonous working hours and inadequate rest [ 66 , 68 , 69 ]; long working hours per day (i.e. more than ten) were significantly associated with emotional exhaustion and sleepiness [ 32 ] and those on night shift reported significantly more mental fatigue and lack of energy than those on day shift [ 30 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher job satisfaction of ratings relative to officers/engineers in this study may therefore possibly be accounted for by greater social support amongst ratings. Support for this explanation is provided by the qualitative findings of a related study (McVeigh et al, 2018), whereby two superintendents indicated that ratings experienced a better social life on-board than officers due to ratings’ fixed meal times, their homogenous nationality, and the set-up of their mess/social area on-board, as exemplified by a superintendent’s observation: “For the crew, for the Filipino lads... they get together more as a group... The social interaction is gone at officer level.” Therefore, ratings’ higher job satisfaction levels relative to officers/engineers may possibly be explained in terms of more cohesive relationships with peers.…”
Section: Discussionmentioning
confidence: 86%
“…This study provides a quantitative analysis of the effects of the programme. A related qualitative study of this programme [110] found that participants reported positive perceptions of the programme, but also communicated criticisms, many of which were underpinned by the need to adapt the programme to the unique context on board. Specifically, a number of participants reported that the personal nature of the programme was an uncomfortable experience on board; a lack of time for the programme; and the need for trained facilitators.…”
Section: Effects Of the Pilot Psychosocial Programmementioning
confidence: 99%
“…Notably, many of these concerns raised by these programme participants may be addressed through the use of computer-based psychosocial interventions on board, which could be completed in the individual's own time, privacy, and even language. Online or computer-based psychosocial interventions and training lend themselves to the isolated and dispersed context of seafaring [110]. Numerous Internet-based interventions have been tested for common psychological disorders, and research indicates that they frequently lead to similar outcomes as face-to-face psychotherapy, alongside being cost-effective [111].…”
Section: Effects Of the Pilot Psychosocial Programmementioning
confidence: 99%